The degree to which Arabic language teachers in Ajloun Governorate possess e-learning skills - Alfrehat, Rodina Mohammad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree to which Arabic language teachers in Ajloun governorate possess e-learning skills. The study relied on the analytical descriptive approach. The study population consisted of approximately (372) male and female teachers, and the study sample consisted of (82) male and female teachers, who were chosen randomly. The results of the study showed that the degree of possession of Arabic language teachers in public schools in Ajloun governorate came at a high level, with a mean of (3.67), The educational level and job experience, and the results showed that there were statistically significant differences to the degree to which teachers possess e-learning skills according to the variable of social status and in favor of the single category. The study recommended holding workshops for teachers; In order to get acquainted with e-learning and to make them aware of the importance of this system and the mechanism of dealing with it, to train teachers in the use of computers, the Internet and e-learning skills, and to design flexible educational curricula in which activities, exercises and lessons take into account both formal learning and e-learning.